Role of Logistics and Transport Sector in Globalization: Evidence from Developed and Developing Economies - Muhammad Ejaz; Ayesha Naz (Sir Syed University Research Journal of Engineering and Technology)
This study identifies the influence of transportation sector in driving the process of globalization across globe. Various studies have theoretically described this factor but literature has yet to come up with some empirical findings to recognize its role as a cause of globalization. Hence, present study has proposed a systematic theoretical framework by taking into account three modes of transportation including air, rail and marine to establish their relationship to globalization over the period of 1995 to 2020.  Cointegration results validate long run association between globalization and the modes of transportation. Further, generalized method of moments (GMM) estimates is applied by dividing the data into three regions.  The data of 109 developed and developing countries shows that all the three modes of transportation are significant in shaping the process of globalization worldwide. In case of 77 developing countries, rail and marine transport are significant while in 32 developed countries only marine transport is appeared to be a significant contributor in formulating the trend of globalization. It is important to note that the role of marine transport is more influential in determining the intensity, expansion and improvement of global networks.